The Scythian Stag in Contemporary Arts and Craft: Tuva and Abroad - Leung, Katherine Zeahan (The New Research of Tuva, 2021)
The article examines the interest in Scythian imagery and motifs in contemporary arts and crafts, both in Tuva and outside Russia, on a surge after the excavation of Arzhan II burial site. As proved by numerous references, the most popular of the Arzhan II finds was the stylized image of the Scythian stag on a golden hair pin. It has since appeared on the photo taken by Russian photographer Andrei Bronnikov, whose main subject is jewelry. Tattoo artists in English-speaking regions have seen an uptick in customers requesting Scythian stag tattoo designs, due in large part to the discovery of the popularly dubbed “Ukok Princess” and increase in interest in prehistoric fantasy media. Russian-speaking fashion designers redefine textile and ornament in the twenty-first century, influenced by the golden accents of the looped stag in their work, at times inventing an embellished narrative of the past. Folk crafters have created costume and jewelry designs for a different world they wish to inhabit, even creating alter-egos and stories that accompany Scythian-inspired pieces. Finally, within Tuva, wood carving continues thanks to trailblazers that promote folk handicrafts through education and archival work.Artists around the world are fascinated by this unique relic of the past and employ the symbol in romantic imaginings of their past and present.
Keywords: Scythian gold; Scythian stag; Scythian imagery; Tuva; Tuvan culture; contemporary art; photography; tattoo; folk art; fashion; national costume; textile; wool felt; wood carving